Tribological Behaviour Study Of Aluminium Metal Matrix Composites For Automotive Brake Rotor Applications - Karim, Md. Rezaul (2007)
Use of light-weight materials in auto components is a cutting edge research interest. The auto brake rotor which is traditionally made from cast irons is an attractive candidate for material substitution. Aluminium alloy based metal matrix composites (AL-MMC) with ceramic particulate reinforcement have shown great promise for such applications.